Differential regulation of mTORC2 signalling by type I and type II calreticulin (CALR) driver mutations of myeloproliferative neoplasm - Saadia Naseer; Aditi Singh; Saurabh Shrivastva; Rishi Kant Singh; Shayeri Chowdhury; Chinmoy Sankar Dey; Anita Roy (Cell Communication and Signaling)
Abstract Calreticulin (CALR) is an endoplasmic reticulum chaperone. Frameshift mutations in CALR were discovered in patients with myeloproliferative neoplasm showing increased platelet counts. The frameshift was observed in the last exon of CALR, leading to a novel C-terminal tail. Calreticulin mutations were categorised into Type I and Type II depending upon the extent of retention of CALR WT sequences. Clinically, Type I mutations induced myelofibrosis, while Type II mutations were associated with early onset of the disease. Both mutations induced ligand-independent activation of the thrombopoietin receptor (TpoR) and consequently enhanced platelet production. However, no specific difference in signalling mechanism could be demonstrated between them. Using over-expression of CALR WT, CALR ∆52 (Type I) and CALR ins5 (Type II) in HEK cells, we showed that Type I CALR mutations downregulated the basal mTORC2 signalling without affecting mTORC1. The decrease in basal mTORC2 signalling was attributed to CALR ∆52-induced increased expression of c-JUN through occupation of the enhancer sequences of jun. Furthermore, increased c-JUN expression decreased the expression of RICTOR, a component of mTORC2. Strikingly, overexpression of RICTOR or knockdown of c-JUN reversed the inhibitory effect of CALR ∆52 on mTORC2 activity. Finally, we demonstrated that CALR ∆52 decreased the glucose uptake and cellular ATP levels in a c-JUN-mTORC2-dependent manner. These findings not only contribute to our understanding of the molecular mechanisms underlying mutant CALR driven myeloproliferative neoplasm but also provide potential therapeutic targets against the disease. Graphical abstract